2000
DOI: 10.1002/(sici)1097-0231(20000430)14:8<624::aid-rcm922>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cyclodextrin-barbiturate noncovalent complexes using electrospray ionization mass spectrometry and capillary electrophoresis

Abstract: Various noncovalent complexes between native and derivatized cyclodextrins (CDs) and barbiturates were studied using capillary electrophoresis (CE) and electrospray ionization mass spectrometry (ESI-MS). This paper involves the study of four aspects of CD-barbiturate noncovalent inclusion complexes. The first study focused on determining the formation of CD-barbiturate inclusion complexes in ESI-MS. This determination was accomplished by the comparison of migration data from CE with ESI-MS inclusion complex pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…Previously, the formation of true host-guest inclusion com- plexes with ␤-CD had been reported [3,25]. As observed in this study, the presence of an additional heterocyclic moiety in the anesthetic structure enhances the binding with the ␤-CD.…”
Section: Formation Of Specific Local Anesthetic-cd Noncovalent Complexessupporting
confidence: 63%
See 3 more Smart Citations
“…Previously, the formation of true host-guest inclusion com- plexes with ␤-CD had been reported [3,25]. As observed in this study, the presence of an additional heterocyclic moiety in the anesthetic structure enhances the binding with the ␤-CD.…”
Section: Formation Of Specific Local Anesthetic-cd Noncovalent Complexessupporting
confidence: 63%
“…A previous study performed in this lab showed the formation of specific non-covalent complexes of a group of acidic hypnotic agents [3]. In this study, we extend this approach to a group of basic local anesthetics in an attempt to determine whether the behavior previously observed was limited to the acidic compounds or is more universal in its applicability.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…The OMT, DMT, DDVP, CBF, FEN DZP, EST, ALP, TAL, CLP and PNG were sensitive in PI mode, whereas the analysis of the BBT and PNB was carried out in NI mode because they were not possible to be optimized in the PI mode according literatures. 46,47 In order to select precursor ions for each analyte, chromatograms were recorded in the full scan mode. In this work, protonated molecular ions for DMT, OMT, DDVP, CBF, Table 2.…”
Section: Lc-esi-ms/msmentioning
confidence: 99%